EVALUATION OF OSB PANELS USING RESIDUAL WOOD WITH LOW CONTENTS OF CASTOR OIL POLYURETHANE RESIN - Barbirato, Guilherme Henrique Ament; Lopes, Wanley Eduardo; Martins, Romulo Henrique Batista; de Campos, Cristiane Inácio [UNESP]; Fiorelli, Juliano (Universidad del Bio Bio, 2024)
The use of residues from human activities has been currently gaining ground in the national and international markets, aiming toward the production of more sustainable materials that are less aggressive to the environment. Reusing and adding value to new products has also become an important factor in reducing production costs and the best alternative for this is process optimization. The choice for residual balsa wood was due to its rapid growth and low density, as well as for its ease of engineering and determining the ideal amount of resin for different types of panels. This study aims to investigate the influence of the content variation of castor oil-based polyurethane resin on the physical and mechanical properties of OSB board particles made from residual balsa wood in reforestation areas. The panels were produced with 8, 10, and 12 % commercial castor oil-based polyurethane resin and 9 mm long particles; their physical and mechanical characterizations followed international normative recommendations. The results indicated that the panels with resin contents higher than 10 % reached the minimum regulatory requirements for type 2 OSB panels, suitable for structural application. On the other hand, the panels produced with 8 % resin reached the minimum requirements for type 1 OSB panels, suitable for non-structural use by the furniture industry, such as linings and partitions. Therefore, our study concludes that the variation of resin contents for OSB panels of residual balsa wood allowed us to achieve optimal levels for the use of castor oil-based polyurethane resin, reaching minimum values recommended by regulations for OSB panels type 1 and 2 and a great possibility of application of this product for engineered materials.
Keywords: Balsa wood; mechanical properties; organic resin; Oriented Strand Board; physical properties